Forensic supportive housing programs: a scoping review - Grachev, Kira; Kerman, Nick; Simpson, Alexander Ian Frederic; Igoumenou, Artemis; Wilkie, Treena; Stergiopoulos, Vicky (Frontiers in Psychiatry, 2026)
IntroductionForensic supportive housing (FSH) aims to support community reintegration and recovery of forensic psychiatric patients, while managing community risks. Although FSH is critical to the recovery process, the literature on FSH models and their outcomes is scant. A registered scoping review was undertaken to identify the models and outcomes of FSH internationally, and identify research gaps.MethodsSeven academic databases (Medline, Embase, PsycINFO, CINAHL Plus, Web of Science, Ebsco CINAHL, Ebsco Criminal Justice Abstracts, ProQuest) were searched, in addition to backward and forward citation searching. FSH models (program philosophy; support components and staffing composition) and their outcomes (e.g., re-hospitalization; re-offending; housing placement; well-being and quality of life) were examined.ResultsA total of 4,084 articles were initially screened. Following full-text review of 82 articles, and citation searching, a total of 18 articles were included in the review. Most studies were descriptive. The program models identified varied in aims, program philosophy, and staffing models. Although most studies were uncontrolled, existing evidence suggests that FSH can support successful community tenures, and reduce risk of re-offending. Relationships with staff and fellow residents, along with opportunities to cultivate practical skills and self-efficacy, were identified as contributors to resident satisfaction in FSH. However, concerns of trans-institutionalization and limited resident autonomy and choice around housing options were identified in some settings, highlighting the need for greater attention to these programs.ConclusionResearch on FSH, an essential support for the successful community reintegration of forensic patients, is limited. Although existing literature highlights promising health, housing, and justice outcomes associated with FSH settings, more research is needed to establish best practices and support mental health recovery and safeguard the human rights of this population.